Keuntungan Usaha Kue Bagea Sheren MU Di Kelurahan Buyungon Kecamatan Amurang Kebupaten Minahasa Selatan - Batz, Jeinivertz Meilano De; Baroleh, Jenny; Kaunang, Rine (Sam Ratulangi University, 2024)
This study aims to analyze the business profits of Sheren MU Bagea Cake in Buyungon Village Amurang District South Minahasa Regency. The research lasted for 2 months from May to June 2023. The data collected were primary data obtained from direct interviews with entrepreneurs of Sheren MU Bagea Cake, using questionnaires. Secondary data were obtained from journals, research reports taken from the internet. The results of the study were analyzed descriptively with profit analysis. The results showed that the amount of net profit from the Sheren MU business in Buyungon Village, Amurang District, South Minahasa Regency was IDR3,061,683 per week, in a month of IDR12,246,732, and in a period of 1 year it was IDR146,960,784.